Industrial democracy : strategies for community revitalization - Woodworth, Warner; Meek, Christopher; Whyte, William Foote (Beverly Hills : Sage Publications, 1985)
Industrial Democracy is one of the first attempts to explain a newly developed field: the theory and practice of countering industrial decline and subsequent deterioration of the quality of community life. The contributors give an overview of the problem of economic dislocation, and explore the social responsibility of corporations towards surrounding communities.
Part I. The problems of economic dislocation: an overview -- Part II. Revitalization through labor-management cooperation -- Part III. Forms of community-worker ownership -- Part IV. Prospect for revitalization: barriers and resources.
Includes index.
Keywords: URBAN ECONOMICS; COMMUNITY DEVELOPMENT, URBAN -- UNITED STATES; INDUSTRIES -- SOCIAL ASPECTS -- UNITED STATES; EMPLOYEE OWNERSHIP -- UNITED STATES; URBAN RENEWAL -- UNITED STATES